Effects of music training on executive functions in preschool children aged 3–6 years: systematic review and meta-analysis - Lu, Yanan; Shi, Lin; Musib, Ahmad Faudzi (Frontiers in Psychology, 2025)
BackgroundExecutive functions is a crucial ability in the early development of preschool children. While numerous studies have found that music training has a favorable effect on children’s executive functions, there is a lack of a consistent perspective on this topic, particularly with regard to the dose–response relationship.MethodsSystematic searches were conducted of Web of Science, PubMed, Scopus, and China National Knowledge Infrastructure. A random-effects meta-analysis was used to compute standardized mean differences (SMD) and 95% confidence intervals (CI).ResultsIn all, 10 studies were included in the meta-analysis, in which children’s music training groups showed significantly improved inhibitory control (SMD = 0.38, 95% CI: 0.16–0.6), working memory (SMD = 0.35, 95% CI: 0.16–0.54), and cognitive flexibility (SMD = 0.23, 95% CI: 0.04–0.42) in comparison with control groups. Subgroup analyses indicated significant improvements relative to the control groups for inhibitory control following music training having a duration of ≥12 weeks (SMD = 0.51, 95% CI: 0.22–0.8), occurring ≥3 times per week (SMD = 0.48, 95% CI: 0.2–0.75), and lasting 20–30 min per session (SMD = 0.42, 95% CI: 0.2–0.63). Significant improvements were seen for working memory following music training having a duration of ≥12 weeks (SMD = 0.42, 95% CI: 0.18–0.65), occurring <3 times per week (SMD = 0.49, 95% CI: 0.06–0.93), occurring ≥3 times per week (SMD = 0.28, 95% CI:0.1–0.47), and lasting 20–30 min per session (SMD = 0.39, 95% CI: 0.16–0.54). Music training significantly improved cognitive flexibility following training having a duration of ≥12 weeks (SMD = 0.22, 95% CI: 0.04–0.41), occurring ≥3 times per week (SMD = 0.19, 95% CI: 0.0–0.39), and lasting >40 min per session (SMD = 0.74, 95% CI: 0.22–1.26).ConclusionMusic training has a positive effect on inhibitory control, working memory, and cognitive flexibility in preschool children aged 3–6 years. This effect is influenced by certain training factors, including the duration of the intervention period, frequency per week, and length of each session.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/#aboutregpage, CRD42024513482.